Minimally invasive management of central ECMO after ascending aortic surgery. Issue 3 (9th January 2019) - Lorusso, Roberto; Bidar, Elham; Natour, Ehsan; Heuts, Samuel
Abstract: A small percentage of ascending aortic surgical procedures require temporary mechanical circulatory support, of which veno‐arterial extracorporeal membrane oxygenation (V‐A ECMO) is the most established technique. We present a surgical technique for minimally invasive central V‐A ECMO management, avoiding resternotomy or ventricular compression, while maintaining antegrade blood flow and permitting sternal closure following ascending aortic surgery.